A Retrospective Analysis of the Use of 3-Factor Prothrombin Complex Concentrates for Refractory Bleeding After Cardiopulmonary Bypass in Children Undergoing Heart Surgery: A Matched Case-Control Study. (September 2020) - Harris, Andrea D.; Hubbard, Richard M.; Sam, Rebecca M.; Zhang, Xu; Salazar, Jorge; Gautam, Nischal K.
The 3-factor prothrombin complex concentrate (3FPCC) may be used off-label to treat refractory bleeding during cardiac surgery in children. This retrospective study examined the rate of clinical complications following the use of 3FPCC. Patients treated with 3FPCC were matched to controls for age, gender, prematurity, weight, cardiopulmonary bypass times, and cross-clamp times. Fifty-nine cases were individually matched to 59 controls based on propensity scores. 3FPCC was not associated with an increased risk of thromboembolic events, mortality, or need for postoperative extracorporeal membrane oxygenator support. These results suggest the safety of 3FPCC when used for refractory bleeding after cardiopulmonary bypass in children undergoing congenital heart surgery.